Secure Connectivity Using Image Steganography Theme Cyber Security - PROF.MRS.SARITA DHAWALE. (International Journal of Pharma and Bio Sciences, 2011)
Providing Information security for client authentication over a network in a client/server environment is critical issue. Authenticated connection establishment between client and server requires password verification, in which client provides the password and server verifies it. Successful password verification initiates the client/Server to perform secured request/reply mechanisms. Hence there is need for confidential transmission of password in an unsecured network. Steganography is the art and science of writing hidden messages in such a way that no-one apart from the sender (client) and intended recipient(Server) even realizes there is a hidden message. The term Steganography includes the concealment of digital information within computer files. Generally a Steganography messages will appear to be something else: a picture, an article, a shopping list, or some other message.Steganography techniques can be used for providing confidentiality of password. This paper intends to give an overview of image steganography, its uses and techniques. It also attempts to identify the requirements of a good steganographic algorithm and briefly reflects on which steganographic techniques are more suitable for which applications. In this paper I would like to focus on the most secured connection establishment for client/Server Environment. Characters provided by the client as a password are appended in to an image using Steganography technique. Appended image containing password Is transmitted over network to reach the server. Server retrieves the original password decoding algorithm .Server verifies and authorizes the client for connection establishment. Even if the intruder steals the images over the network he/She will not be able to decode the password from the image.